2021
DOI: 10.1261/rna.078935.121
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing regulation of cell-cycle genes by SPF45/SR140/CHERP complex controls cell proliferation

Abstract: The regulation of pre-mRNA processing has important consequences for cell division and the control of cancer cell proliferation but the underlying molecular mechanisms remain poorly understood. We report that three splicing factors, SPF45, SR140 and CHERP form a tight physical and functionally coherent complex that regulates a variety of alternative splicing events, frequently by repressing short exons flanked by suboptimal 3' splice sites. These comprise alternative exons embedded in genes with important func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 69 publications
2
21
0
Order By: Relevance
“…This discrepancy might be due to the different cell types used in both analyses. This possibility is supported by the recent findings that CHERP depletion in Hela cells frequently caused retained intron events [ 24 ] and implies that CHERP regulated the alternative splicing in a cell-specific manner. In our analysis, weak or suboptimal splice sites, high GC content in introns, and short intron lengths were important and common features of intron retention.…”
Section: Discussionsupporting
confidence: 62%
“…This discrepancy might be due to the different cell types used in both analyses. This possibility is supported by the recent findings that CHERP depletion in Hela cells frequently caused retained intron events [ 24 ] and implies that CHERP regulated the alternative splicing in a cell-specific manner. In our analysis, weak or suboptimal splice sites, high GC content in introns, and short intron lengths were important and common features of intron retention.…”
Section: Discussionsupporting
confidence: 62%
“…Among the OTCD mouse models, the mouse spf ash is characterized by the c.386G>A splicing mutation and it has been exploited to evaluate replacement gene therapy approaches (Moscioni et al 2006 ; Wang et al 2011 , 2012 ; Cunningham et al 2013 ). This animal model represents therefore an ideal pre-clinical platform to assess the therapeutic potential of RNA therapeutics based on engineered variants of the spliceosomal U1snRNAs, which were proven to be capable, both in cellular (Glaus et al 2011 ; Schmid et al 2013 ; Scalet et al 2017 , 2018 , 2019 ; Martínez-Pizarro et al 2018 ; Balestra et al 2019a , b ; Martín et al 2021 ) and animal (Balestra et al 2014 , 2016 , 2020b ; Dal Mas et al 2015 ; Rogalska et al 2016 ) models of human diseases, to counteract splicing mutations and force exon recognition, thus rescuing gene expression. Recently, a U1snRNA variant, upon delivery via an Adeno-Associated virus Vector in spf ash mice, partially restored OTC expression at RNA and protein level in liver (Balestra et al 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Among molecules acting at RNA levels, engineered variants of the U1snRNA, the RNA component of the spliceosomal U1 ribonucleoprotein (U1snRNP) mediating 5′ss recognition and thus exon definition in the earliest splicing steps (De Conti et al 2013 ), have proven to be effective in modulating splicing for therapeutic purposes. In particular, U1snRNA variants with increased complementarity with the 5′ss of the defective exon (named compensatory U1snRNA), or targeting the downstream intronic sequences (named Exon specific U1snRNA, ExSpeU1), have demonstrated their ability to rescue exon skipping caused by different types of mutations in cellular and animal models of several human diseases (Donadon et al 2018 , 2019 ; Scalet et al 2018 , 2019 ; Yamazaki et al 2018 ; Balestra et al 2019a , 2020a ; Lee et al 2019 ; Donegà et al 2020 ; Martín et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to DNA and proteins, RNAs are also substrates for chemical modifications (24). N 6 methyladenosine (m 6 A), the most abundant internal modification in eukaryotic mRNA, has been shown to influence AS (25)(26)(27)(28). m 6 A is co-transcriptionally deposited by the methyltransferase-like 3 (METTL3) and METTL14 methyltransferase complex, which partially localizes to nuclear speckles, where splicing occurs (29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…N 6 methyladenosine (m 6 A), the most abundant internal modification in eukaryotic mRNA, has been shown to influence AS (25)(26)(27)(28). m 6 A is co-transcriptionally deposited by the methyltransferase-like 3 (METTL3) and METTL14 methyltransferase complex, which partially localizes to nuclear speckles, where splicing occurs (29)(30)(31). It has been shown that depletion of the Drosophila METTL3 methyltransferase homologue, results in altered AS patterns that influence sex determination (32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%